Right supernumerary kidney: A rare entity - Kumar, Manjeet (Urol Case Rep, 2019)
The supernumerary kidney especially on right side is a rare diagnosis. Only few case reports are documented in literature. We report a case of Right supernumerary kidney with partial fusion of right accessory kidney to upper kidney.